Using fly ash treated by NaOH and H2SO4 solutions for Hg2+ and Cd2+ ion adsorption - Chinh, Nguyen Thuy; Mai, Tran Thi; Thu Trang, Nguyen Thi; Thanh Huong, Nguyen Thi; Hoang, Thai (Vietnam Journal of Chemistry, 2017)
This paper presents the results of adsorption ability of heavy metal ions (Hg2+ and Cd2+) by fly ash (FA) before and after treatment using NaOH and H2SO4 solutions.  Original- and treated FA were characterized by Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), and Scanning Electron Microscope (SEM). Specific surface area of FA before and after treatment was calculated by Brunauer – Emmett – Teller (BET) isotherm equation. The obtained results indicated that the morphology and specific surface area of FA changed clearly after treatment by acid or alkaline solutions. Adsorption capacity the Hg2+ and Cd2+ ion by FA was determined from data of UV-Vis spectra. After treatment, the adsorption capacity of ions by FA increased remarkably in comparison with non-treated FA. The FA treated by NaOH solution has the adsorption capacity higher than FA treated by H2SO4 solution. The maximum adsorption capacity of the FA treated by NaOH solution for Cd2+ and Hg2+ ions at room temperature is 28.97 and 14.60 mg/g, respectively. The equilibrium adsorption data were described by the Langmuir and Freundlich isotherm models. The results showed that equilibrium data were fitted well to the Langmuir isotherm. Keywords. Fly ash, treatment, adsorption capacity, heavy metal, Langmuir isotherm